THE EFFECT OF TRAINING AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE IN THE OFFICE OF THE INDONESIAN ENVIRONMENTAL AND FORESTRY RESEARCH AND DEVELOPMENT CENTER IN MAKASSAR - Fahruni Khaerunnisa; Muh Asdar; Kurniawan (Universitas Ichsan Sidenreng Rappang, 2023)
The purpose of this study was to test and analyze the effect of training and work motivation on employee performance at the Makassar Research and Development Center for Environment and Forestry. Data collection uses primary data obtained from questionnaires using saturated sampling techniques. The population is all permanent employees at the Makassar Research and Development Center for Environment and Forestry with a total of 51 people. The results of the questionnaire have been tested for validity and reliability, and the classical assumptions in the form of normality assumptions and heteroscedasticity assumptions have been tested. Methods of data analysis using multiple regression techniques. The results showed that the proposed hypothesis was accepted because it showed positive and significant results of hypothesis testing. This means that Training and Work Motivation have a positive and significant effect on Employee Performance.